Melamine Hydroiodide Functionalized MAPbI3 Perovskite with Enhanced Photovoltaic Performance and Stability in Ambient Atmosphere. Issue 1 (23rd November 2018) - Yang, Fu; Kamarudin, Muhammad A.; Hirotani, Daisuke; Zhang, Putao; Kapil, Gaurav; Ng, Chi Huey; Ma, Tingli; Hayase, Shuzi
Abstract : Despite the remarkable performance of organometallic halide perovskite solar cells (PSCs), their ultimate stability is still a major issue that inhibits the commercialization of this eminent technology. Herein, melamine hydroiodide (MLAI) is added to function methyl ammonium (CH3NH3 +, MA + ) lead iodide perovskite for fabricating structured perovskite with enhanced photovoltaic performance and stability in the harsh ambient atmosphere (35 °C, 60–70% relative humidity). Nearly no new phase formed even incorporated 25 mol.% MLAI induces the strain in the perovskite crystal structure. The MLAI‐structured perovskite film shows a denser and smoother surface than the pristine MAPbI3 perovskite. Planar PSCs based on 2 mol.% MLAI‐functionalized perovskite show 17.2% power conversion efficiency with nearly no hysteresis which is much higher than pristine MAPbI3 PSCs. Most importantly, the solar cell devices based on 2 mol.% MLAI‐functionalized perovskite still retain over 90% of the initial performance after being kept in ambient atmosphere for more than 560 h without encapsulation. Abstract : Melamine hydroiodide (MLAI) has been successfully introduced for preparing hetero structured MAPbI3 perovskite for enhancing the photovoltaic performance and stability of perovskite solar cells in a robust humid ambient atmosphere (35 °C, 60–70% relative humidity). The power conversation efficiency of perovskite solar cells based on MLAI functionalized perovskite is 25% higher than that of pristine MAPbI3 perovskite with nearly no hysteresis and high stability.